Effect of Diet on Adult House Fly (Diptera: Muscidae) Injected With the Salivary Gland Hypertrophy Virus (MdSGHV). Issue 3 (9th May 2018) - Schaler, Jennifer; Stoffolano, John; Fausto, Anna Maria; Gambellini, Gabriella; Burand, John
Abstract: Research to date on the salivary gland hypertrophy virus (SGHV) in three species of flies has focused on adult flies having access to and taking a proteinaceous diet. Since many studies have shown that diet affects viral infection in numerous organisms, this study examined the effect of a protein-free diet on the effect of the SGHV virus in adult house flies, Musca domestica . L. Adults infected with the virus, and maintained on a sugar diet only, showed salivary glands with a blue rather than a grayish color and mild hypertrophy compared with protein-fed flies. It was possible to retrieve the virus from these glands and successfully infect noninfected flies. When injected at various ages, female flies fed only sugar showed that regardless of age, sugar-fed flies still became infected and showed the pathology of the glands. In addition, electron microscope studies revealed at the ultrastructural level that there was no difference between viral replication in cells from salivary glands of adults fed a proteinaceous-free diet and those feeding on protein.